Ant Colony Optimisation for multi-level assembly job shop scheduling. (21st September 2009) - Omkumar, M.; Shahabudeen, P.
Job shop scheduling is one of the most explored areas in the last few decades. Although it is very commonly witnessed in real-life situations, very little investigation has been carried out in scheduling operations of multi-level jobs, which undergo serial, parallel, and assembly operations in an assembly job shop. In this work, some of the dispatch rules, which have best performances in scheduling multi-level jobs in a dynamic assembly job shop, are tested in static assembly job shop environment. A new optimisation heuristic based on the Ant Colony Algorithm is proposed and its performance is compared with the dispatch rules. [Received 14 July 2008; Revised 11 February 2009; Accepted 16 April 2009]